First description of the male of Dendrothrips karnyi (Thysanoptera, Thripidae) - Minaei, Kambiz; Rashid, Zeinab; Ramezani, Leila; Sohani, Nooshin Zandi (Zootaxa, 2020)
Dendrothrips is one of 12 genera currently recognised in subfamily Dendrothripinae (ThripsWiki 2020). The species of Dendrothrips have the fore wing anteromarginal cilia arising ventrally behind the margin, but in contrast to species in other genera with this character state the wing apex is recurved without a terminal seta (Mound & Tree 2016). Species of Dendrothrips breed on leaves, and many have been recorded from species of plant family Oleaceae (Marullo 2003). The species of Dendrothrips are recorded from Europe to Australia, including Africa and Asia. In Iran so far, six species are known in the genus, including: D. aspersus Bhatti, D. degeeri Uzel, D. jasminum Ramakrishna & Margabandhu, D. karnyi Priesner, D. phyllireae (Bagnall) and D. saltator Uzel (Alavi et al. 2014, Minaei 2015, Mirab-balou & Dosty 2015). Recently the male of D. aspersus was described from Fars province, Iran (Minaei 2017), and the aim here is to describe the previously unknown male of D. karnyi, based on specimens collected in Ilam province, western Iran. Females of D. karnyi are recorded from Poland and northern Italy to Croatia and Turkey, but the male has remained unknown (zur Strassen 2003). Females have previously been recorded from Iran (Bagheri & Alavi 2007), but we recently collected one male with a series of females from Vitex agnus-castus, the host plant indicated by zur Strassen (2003).